The Burial Record of Prehistoric Liangshan in Southwest China : Graves as Composite Objects - Hein, Anke (Springer International Publishing : Imprint: Springer, 2017)
This book proposes a new model and scheme of analysis for complex burial material and applies it to the prehistoric archaeological record of the Liangshan region in Southwest China that other archaeologists have commonly given a wide berth, regarding it as too patchy, too inhomogeneous, and overall too unwieldy to work with. The model treats burials as composite objects, considering the various elements separately in their respective life histories. The application of this approach to the rich and diverse archaeological record of the Liangshan region serves as a test of this new form of analysis. This volume thus pursues two main aims: to advance the understanding of the archaeology of the immediate study area which has been little examined, and to present and test a new scheme of analysis that can be applied to other bodies of material.
Keywords: Social sciences.; Archaeology.; elektronické knihy; electronic books